2016
DOI: 10.1002/gcc.22347
|View full text |Cite
|
Sign up to set email alerts
|

HRAS mutation prevalence and associated expression patterns in pheochromocytoma

Abstract: Pheochromocytomas (PCC) and abdominal paragangliomas (PGL) display a highly diverse genetic background and recent gene expression profiling studies have shown that PCC and PGL (together PPGL) alter either kinase signaling pathways or the pseudo‐hypoxia response pathway dependent of the genetic composition. Recurrent mutations in the Harvey rat sarcoma viral oncogene homolog (HRAS) have recently been verified in sporadic PPGLs. In order to further establish the HRAS mutation frequency and to characterize the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A review of the English literature indicated a much lower BRAF and HRAS mutation rate in ordinary PCC/PGL and no concomitant mutations were reported ( 4 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). For ordinary GN, it is not usually associated with genetic abnormalities, and only RET gene has been considered to be causative in its pathogenesis ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…A review of the English literature indicated a much lower BRAF and HRAS mutation rate in ordinary PCC/PGL and no concomitant mutations were reported ( 4 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). For ordinary GN, it is not usually associated with genetic abnormalities, and only RET gene has been considered to be causative in its pathogenesis ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Somatic mutations in other genes may also activate downstream pathways. For example, RAS mutations have been described in pheochromocytomas and paragangliomas ( 47 , 48 ). These mutations predict a constitutive activation of the mitogen-activated protein kinase and phosphoinositide 3-kinase (PI3K) pathways, leading to abnormal proliferation of pheochromocytoma and paraganglioma cells.…”
Section: The Hallmarks Of Cancer and Mppgmentioning
confidence: 99%
“…These mutations predict a constitutive activation of the mitogen-activated protein kinase and phosphoinositide 3-kinase (PI3K) pathways, leading to abnormal proliferation of pheochromocytoma and paraganglioma cells. RAS mutations have not, however, yet been associated with a clear MPPG phenotype ( 47 , 48 ).…”
Section: The Hallmarks Of Cancer and Mppgmentioning
confidence: 99%
“…PPGL are commonly associated with germline and/or somatic mutations in the susceptible genes resulting in these tumors. More than a third of these tumors are associated with at least one of the common germline mutations, including VHL , RET , NF1 , MAX , SDHA , SDHB , SDHC , SDHD , SDHAF2 , and TMEM127 genes, and about 25% to 30% are associated with somatic mutations, such as RET , VHL , NF1 , MAX , EPAS1/HIF2A , and Harvey rat sarcoma viral oncogene homolog ( HRAS ) genes [1, 1216]. Some of these somatic mutations are linked with the processes involved in hypoxia adaptation.…”
Section: Genetic Susceptibility For Ppglmentioning
confidence: 99%